Neutronic Design for Heat Pipe Reactor With Annular and Accident Tolerant Fuels - Cai, Boshuai; Chen, Shengli; Wu, Tianfan; Wang, Yujing; Zhang, Zhaozhan; Yuan, Cenxi; Zhang, Chunyu; Ge, Yulin (Frontiers in Energy Research, 2021)
Several core designs of heat pipe reactors with megawatt power were proposed for extreme environments, such as the deep space, the deep sea, and the earthquake locations. However, the existing designs have either the difficulty of manufacture or potential issues of transport. In the present work, a heat pipe design is proposed with an annular fuel element to replace the cylindrical and hexagon fuel elements. In addition, candidate accident tolerant fuels, such as the UN and U3Si2 fuels, are implemented. The neutronic properties of the new reactor design are systematically investigated by the OpenMC Monte Carlo code simulations. It is found that BeO presents a better effect of reducing the axial power deviation than Al2O3. The criticality of the proposed design is verified by two configurations of control drums. The depletion calculations show that each design can operate for decades of years.